Pulse pressure and all-cause mortality in ischaemic heart failure patients: a prospective cohort study. (31st December 2022) - Qiu, Weida; Xiao, Xiaoju; Cai, Anping; Gao, Zhiping; Li, Liwen
Abstract: Background: Whether the association between pulse pressure (PP) and mortality varies with systolic blood pressure (SBP) in ischaemic heart failure (HF) with left ventricular systolic dysfunction (LVSD) is unknown. Objective: To evaluate the association between PP and all-cause mortality in ischaemic HF patients with SBP status at admission. Patients and methods: This prospective cohort study included 1581 ischaemic HF patients with LVSD. A total of 23.3% ( n = 368) and 22.2% ( n = 351) of the participants had SBP <110 mmHg and SBP >140 mmHg, respectively, with more than 80% of participants being male. Restricted cubic spline was performed to determine whether a nonlinear relationship existed between PP and all-cause mortality risk. A multivariable Cox proportional hazards model was used to assess the association between PP and all-cause mortality. Results: After a median of follow-up of 3.0 years, 257 events (16.4%) were observed in the cohort. There was a J-shaped relationship between PP and all-cause mortality (P value for nonlinearity = 0.020), with a risk nadir of approximately 46–49 mmHg. All-cause mortality risk varied with SBP status. Higher PP was associated with worse prognosis when the SBP was ≥110 mmHg, whereas the relationship did not reach statistical significance when the SBP was <110 mmHg. Conclusion: A J-shaped relationship between PP and all-cause mortality was observed in ischaemic HF patients with LVSD, and higher PP was associated with worse prognosis only in those with SBP ≥110 mmHg. Further studies are needed to corroborate these findings. KEY MESSAGES: A J-shaped relationship between pulse pressure and all-cause mortality was observed in ischaemic heart failure patients with left ventricular systolic dysfunction, with a risk nadir of approximately 46–49 mmHg. All-cause mortality risk varied with systolic blood pressure status, and higher pulse pressure was associated with worse prognosis when systolic blood pressure was above 110 mmHg.